HENRY JAMES’S MITIGATION OFFICE (Revista de Letras Norte@mentos, 2013)
The present article intends to highlight five propositions in the preface of Henry James’s Theambassadors and compare their suggestions to the literary text. As a result, we will see how oneof the most significant Jamesian novelistic effect, relativism, is linguistically based on thepersistent use of modalizing locutions in both the preface and the novel, mitigating anycategorical interpretation or statement.